Tolerance of KS-4202 soybean to the attack of Bemisia tabaci biotype B (Hemiptera: Aleyrodidae) - Cruz, Patricia L. [UNESP]; Baldin, Edson L. L. [UNESP]; Guimaraes, Leysimar R. P. [UNESP]; Pannuti, Luiz E. R. [UNESP]; Lima, Giuseppina P. P. [UNESP]; Heng-Moss, Tiffany M.; Hunt, Thomas E. (Florida Entomological Soc, 2016)
Bemisia tabaci (Gennadius) biotype B (Hemiptera: Aleyrodidae) is considered one of the most important pests of soybean, Glycine max L. (Merrill) (Fabaceae), in Brazil and worldwide. Although chemical control still represents the principal strategy used to control this insect, less aggressive strategies such as the use of resistant genotypes stand out as potentially efficient alternatives for integrated pest management programs. This study aimed to evaluate the possible occurrence of tolerance to B. tabaci biotype B in the 'KS-4202' soybean genotype, which is already recognized as tolerant to Aphis glycines Matsumura (Hemiptera: Aphididae) in the United States. The 'Conquista' Brazilian cultivar was used as a susceptible control. In a greenhouse, plants (stages V3-V4) of both genotypes were individualized and subjected to 6 patterns of infestation: 1) uninfested and without chemical control; 2) infested and without chemical control; 3) infested and sprayed at 15 d after infestation (DAI); 4) infested and sprayed at 30 DAI; 5) infested and sprayed at 45 DAI; and 6) infested and sprayed at 60 DAI. The study was performed in a completely randomized design with 6 replications for each pattern of infestation. We evaluated the following parameters of productivity: number of pods per plant, dry weight of pods per plant, number of seeds per plant, dry weight of seeds per plant, and dry weight of biomass per plant. A 2-by-2 factorial bioassay was carried out to evaluate the plant responses to whitefly feeding, with 5 replications for each combination. The factors were 2 soybean genotypes ('KS-4202' and 'Conquista') and 2 levels of infestation (0 and 25 pairs), with 4 collection dates of leaflets (7, 14, 21, and 28 DAI). The protein contents and enzyme activities (dismutase superoxide, peroxidase, and polyphenoloxidase) were also determined for each collection date. Whitefly infestation had a negative effect on the weight of seeds and dry weight of biomass of 'Conquista' plants for even the shortest period of infestation (15 d). In contrast, for 'KS-4202', there was no difference in the number of pods per plant, number of seeds per plant, or dry weight of biomass between infested (15, 30, 45, and 60 d) and uninfested plants. Our results demonstrated that the 'KS-4202' genotype is tolerant to B. tabaci biotype B feeding. However, studies are still necessary to better understand the causes of this tolerance because the main factors of tolerance found in this genotype are not the oxidative enzymes studied here.
Keywords: Glycine max; whitefly; host plant resistance to insects; oxidative enzymes